2018
DOI: 10.1016/j.ijpharm.2018.06.054
|View full text |Cite
|
Sign up to set email alerts
|

All disease begins in the gut: Influence of gastrointestinal disorders and surgery on oral drug performance

Abstract: The term "disease" conjures a plethora of graphic imagery for many, and the use of drugs to combat symptoms and treat underlying pathology is at the core of modern medicine. However, the effects of the various gastrointestinal diseases, infections, co-morbidities and the impact of gastrointestinal surgery on the pharmacokinetic and pharmacodynamic behaviour of drugs have been largely overlooked. The better elucidation of disease pathology and the role of underlying cellular and molecular mechanisms have increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 246 publications
(224 reference statements)
0
37
0
Order By: Relevance
“…14 However, dysbiosis can result from challenges such as medications, infections, ageing, lifestyle, surgery and poor nutrition, 14 , 15 In humans, a range of acute and chronic disorders can be a consequence of perturbation of gut microbial communities. [16][17][18] On a chronic basis, inflammatory bowel disease (IBD), obesity and irritable bowel syndrome (IBS) have all been linked to intestinal bacteria and their activities. 10 This aspect opens up the possibility of influencing the microbiota to reduce disease risk, fortify homeostasis and, in some cases, improve therapeutic status.…”
Section: [H1] Human Gut Microbiomementioning
confidence: 99%
“…14 However, dysbiosis can result from challenges such as medications, infections, ageing, lifestyle, surgery and poor nutrition, 14 , 15 In humans, a range of acute and chronic disorders can be a consequence of perturbation of gut microbial communities. [16][17][18] On a chronic basis, inflammatory bowel disease (IBD), obesity and irritable bowel syndrome (IBS) have all been linked to intestinal bacteria and their activities. 10 This aspect opens up the possibility of influencing the microbiota to reduce disease risk, fortify homeostasis and, in some cases, improve therapeutic status.…”
Section: [H1] Human Gut Microbiomementioning
confidence: 99%
“…As a sustained release is achieved, the presence of itraconazole in the amorphous phase would enable the enhanced dissolution and absorption of the drug along the gastrointestinal (GI) tract, which is of importance in the distal GI tract regions (i.e. colon) whereby the intestinal fluid volume is lower (Hatton et al, 2018). The observed solubility enhancement is higher than obtained using an alternative technology (nanosuspension technology) with the same HPC grades and similar drug/HPC ratio, which released only about 20% itraconazole (Konnerth et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is especially of importance in the distal GI tract regions (i.e. colon), whereby the intestinal fluid volume is reduced (Hatton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oral delivery of the medicated diets resulted in 2.9 ppm of FFN and 38 ppm of ERY in fish muscle one day after the last oral treatment (not shown). Antimicrobial tissue concentrations achieved reflect uptake across the intestinal tract (Hatton, Madla, Rabbie, & Basit, ; Hunter & Hirst, ; Lin, Chen, Lin, & Fang, ) and distribution to muscle (Bowser et al, ; Moffitt & Schreck, ; Wang et al, ). Depletion studies of erythromycin A in rainbow trout after oral treatment at 100 mg/kg fish body weight/day for 21 days (Esposito et al, ) revealed a concentration of 0.33 ppm in fish muscle and skin after 10 days.…”
Section: Discussionmentioning
confidence: 99%